Peran Brand Image, Kualitas Produk, Promosi Online dan Tingkat Kepercayaan Produk pada Pengambilan Keputusan Pembelian: Studi Kasus pada CV. Tenun Mulia Gemilang - Galang Eko Prabowo; Vincent Didiek Wiet Aryanto; Mahmud Mahmud; Piji Pakarti (International Forum of Researchers and Lecturers, 2025)
The purpose of this study was to determine how brand image, product quality, online promotion, and product trust level influence consumer decisions to purchase products at CV. Tenun Mulia Gemilang. This study used a questionnaire distributed through social media in the form of Instagram and Whatsapp. This study involved 100 people who were selected randomly. Multiple linear regression analysis was used to analyze the data to evaluate the model between the established variables. The results showed that brand image, product quality, online promotion and product trust level have a significant influence on consumer purchasing decisions for woven products. This study suggests that business actors pay attention to brand image, product quality, and online promotion to increase customer trust and ultimately influence their purchasing decisions. Thus, CV. Tenun Mulia Gemilang can increase consumer product purchasing decisions.